2022
DOI: 10.1016/j.redox.2022.102256
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of lactoferrin aggravates neuronal ferroptosis after intracerebral hemorrhagic stroke in hyperglycemic mice

Abstract: Diabetic hyperglycemia aggravates the prognosis of intracerebral hemorrhagic stroke (ICH) in the clinic. In addition to hematoma expansion and increased inflammation, how diabetic hyperglycemia affects the outcomes of ICH is still unclear. We found that streptozotocin-induced diabetic hyperglycemia not only increased neutrophil infiltration, but also changed the gene expression profile of neutrophils, including lactoferrin (Ltf) encoding gene Ltf . Peroxisome proliferator-activated recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 80 publications
(98 reference statements)
0
24
0
1
Order By: Relevance
“…330231) and used for quantitative PCR in the ABI 7500 Fast Block system (Applied Biosystems, USA). 76 The data were uploaded for analysis to the Qiagen website ( http://www.qiagen.com/geneglobe ). The data were calculated as fold change/regulation using the ΔΔCT method, in which delta CT is calculated between gene of interest and an average of reference genes, followed by ΔΔCT calculations [ΔCT (Test Group) − ΔCT (Control Group)].…”
Section: Methodsmentioning
confidence: 99%
“…330231) and used for quantitative PCR in the ABI 7500 Fast Block system (Applied Biosystems, USA). 76 The data were uploaded for analysis to the Qiagen website ( http://www.qiagen.com/geneglobe ). The data were calculated as fold change/regulation using the ΔΔCT method, in which delta CT is calculated between gene of interest and an average of reference genes, followed by ΔΔCT calculations [ΔCT (Test Group) − ΔCT (Control Group)].…”
Section: Methodsmentioning
confidence: 99%
“…Activating the neutrophil PPAR‐ γ signaling pathway to up‐regulate the expression of Ltf may be beneficial to the treatment of ICH. [ 51 ] In addition, studies have shown that IL‐27 can also regulate the expression of Ltf in neutrophils. Microglia are rapidly activated and secrete a large amount of IL‐27 after ICH.…”
Section: The Pathophysiology Of Ichmentioning
confidence: 99%
“…Tau-mediated iron export inhibits ferroptosis after ischemic stroke [131]. Supplementing lactoferrin reduces the ferroptosis of nerve cells after diabetic ICH [132], while crocin reduces ICH-induced neuronal ferroptosis by increasing Nrf2 expression and nuclear translocation [133]. Dauricine represses nerve cell ferroptosis and brain injury after ICH by up-regulating GPX4 expression [134], while pyridoxal isonicotinoyl hydrazone, a lipophilic iron-chelating agent, alleviates hemorrhage stroke by decreasing ferroptosis and inflammation [135].…”
Section: Strokementioning
confidence: 99%